ANALYSIS OF THE FILM “THE MAN WHO KNEW INFINITY : SPEECH ACT STUDY - Syahrul Effendi Lubis (JELIM : Journal of Education, Language, Social and Management, 2023)
The research method employed was descriptive qualitative research, and the goal of the study was to examine the forms and meanings of speech acts in the film The Man Who Knew Infinity's dialogues. The results show that there are 45 forms and meanings of speech acts in fifteen dialogues containing Locutionary, Illocutionary, and Perlocutionary Acts in the dialogues of Matthew Brown's film "The Man Who Knew Infinity," focusing on the analysis of speech acts of the theory of a British philosopher of language, namely John Langshaw Austin as described in his book "How To Do Things" (1962).